2006
DOI: 10.1055/s-2006-944522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chronic Alcoholic Disease on Magnocellular and Parvocellular Hypothalamic Neurons in Men

Abstract: Although numerous data showing severe morphological impairment of magnocellular and parvocellular hypothalamic neurons due to chronic alcoholic consumption have been gathered from animal experiments, only one study (Harding et al., 1996) was performed on POST MORTEM human brain. This study showed a reduction in the number of vasopressin (VP)-immunoreactive neurons in the supraoptic (SON) and paraventricular (PVN) nuclei, but did not provide any data regarding the effect of chronic alcohol intake on human parvo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 40 publications
2
34
0
1
Order By: Relevance
“…In support of this hypothesis, Silva and colleagues reported that prolonged alcohol intake leads to irreversible loss of oxytocin neurons in the PVN in Wistar rats [66]. In alcoholic humans, post-mortem brains of patients afflicted with chronic alcoholic disease showed increased oxytocin immunoreactivity in the PVN [7]. Very recently, Peters and co-workers have shown that acute intracerebroventricular (ICV) infusion of oxytocin (1 μg/5 μL) attenuated voluntary ethanol self-administration [67].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In support of this hypothesis, Silva and colleagues reported that prolonged alcohol intake leads to irreversible loss of oxytocin neurons in the PVN in Wistar rats [66]. In alcoholic humans, post-mortem brains of patients afflicted with chronic alcoholic disease showed increased oxytocin immunoreactivity in the PVN [7]. Very recently, Peters and co-workers have shown that acute intracerebroventricular (ICV) infusion of oxytocin (1 μg/5 μL) attenuated voluntary ethanol self-administration [67].…”
Section: Discussionmentioning
confidence: 92%
“…Oxytocin neurotransmission is thought to contribute to the activating and reinforcing effects of ethanol and other drugs of abuse [for review, see [3,4]]. Altered oxytocin neurotransmission has been observed in human alcoholics [5][6][7] and in several animal models of alcohol dependence [2,8,9]. It is believed that the oxytocin receptor (OxtR) mediates the involvement of the oxytocin system in psychiatric disorders in general and addiction in particular.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to other classes of drugs of abuse, chronic morphine decreases brain OT synthesis (You et al 2000), chronic ethanol exposure causes degeneration of hypothalamic OT-containing magnocellular neurons (Sivukhina et al 2006) while repeated cocaine administration depletes hippocampal and hypothalamic OT (Sarnyai et al 1992). It is similarly possible that MDMA and GHB might deplete hypothalamic OT to cause alterations in OT-related gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…In alcoholic individuals, plasma OT levels were decreased (39) and OT immunoreactivity was decreased in the magnocellular neurons of the hypothalamus in a post-mortem study (40). Chronic exposure to Δ 9 – tetrahydrocannabinol in rats downregulated OT mRNA expression in the NAc and VTA (41).…”
Section: Evidence That Ot Signaling Is Affected By Drugs Of Abusementioning
confidence: 99%